ПРО ПРАВОВУ ПРИРОДУ ТА ПРАВОВЕ РЕГУЛЮВАННЯ ДОЗВІЛЬНИХ ВІДНОСИН У СФЕРІ ПРИРОДОКОРИСТУВАННЯ ТА ОХОРОНИ НАВКОЛИШНЬОГО ПРИРОДНОГО СЕРЕДОВИЩА - Apanasenko, K.I. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2018)
There is a large list of permissive documents giving for a using of natural resources or for a negative (potentially negative) in fluence on the environment in the Ukrainian legislation. The legal regime of these documents is regulated in special way. Norms of ecological laws state environmental restrictions for users of natural resources, citizens, enterprises and organizations which activity could affect on the environment. The special law in a sphere of permissive relations state principles of the legal regu lation of relations of giving and cancellation of permissive documents for the economic subjects. The Ukrainian law «On administrative services» regulates procedural rules about cooperation of the permissive organs and the economic subjects (as a kind of administrative services). So an actual question is a question about a legal nature of permissive relations in a sphere of ecology that is a main task of the article. This question was not investigated in the economic legal literature in Ukraine. The dominant position of the scientists in a sphere of administrative law is that «permissive activity» in the ecological sphere is a subject for administrative law regulation. Scientists in a sphere of ecological law write about ecological law nature of this legal institute. The author concluded that such relations are economic legal relations, they are a kind of permissive relations in a sphere of economic activity. The object of analyzed relations is a right to realize economic operations / work in a sphere of exploitation of natural resources or such activity that can make an anthropogenic affect on the environment. A subject of the permissive relations in ecological sphere is natural resources, elements of the environment and the whole environment. Difference between subjects of ecological relations and analyzed permissive relations is the next one. The environment and its components are the objects of the legal protection in the ecological relations but they are the objects of the economic activity’s affects in the economic legal relations. REFERENCES: 1. Babiak O.S., Bilenchuk P.D., Chyrva O.Iu. Ekolohichne pravo Ukrainy: navch. posib. Kyiv: Atika, 2000. 216 s. [in Ukrainian].2. Riabets K.A. Ekolohichne pravo Ukrainy: navch. posib. Kyiv: Tsentr uchbovoi literatury, 2009. 438 s. [in Ukrainian].3. Kobetska N.R. Dozvilne ta dohovirne rehuliuvannia vykorystannia pryrodnykh resursiv v Ukraini: dys. ... d-rayuryd. nauk: 12.00.06. Kyiv, 2016. 418 s. [in Ukrainian].4. Mamutov V.K. Posylyty vplyv akademichnoi nauky na formuvannia ekonomichnoho zakonodavstva. Visnyk Natsionalnoi akademii nauk Ukrainy. 2012. No. 7. S. 26-31 [in Ukrainian].5. Shapovalova O.V. Adaptatsiia hospodarskoho zakonodavstva do vymoh staloho rozvytku: avtoref. dys. … d-ra yuryd. nauk: 12.00.04. Donetsk, 2007. 35 s. [in Ukrainian].6. Bobkova A.H. Pravove zabezpechennia rekreatsiinoi diialnosti: avtoref. dys. ... d-ra yuryd. nauk: 12.00.04; 12.00.06. Kyiv, 2001. 34 s. [in Ukrainian].7. Rozovskyi B.H. Korol zhyv. No nuzhdaetsia v lechenyy. Chernyhov: Desna Polyhraf, 2017. 232 s. [in Russian].8. Dzhumaheldyeva H.D. Hozjajstvennoe ispol’zovanie prirodnyh resursov v strukture pravovyh uchebnyh disciplin. Visnyk Donetskoho natsionalnoho universytetu. 2012. No. 2. S. 35-41 [in Russian].9. Shapovalova O.V. Tsilova funktsiia pravovoho rezhymu hospodarskoho vykorystannia pryrodnykh resursiv. Pravo Ukrainy. 2005. No. 10. S. 46-51. [in Ukrainian].10. Vikhrov O.P. Orhanizatsiino-hospodarski pravovidnosyny: monohrafiia. Kyiv: Slovo, 2008. 512 s. [in Ukrainian].11. Shapovalova O.V. Pravove zabezpechennia pidtrymky i rozvytku hospodariuvannia. Luhansk: Vydvo Shidnoukr. nats. untu, 2004. 280 s. [in Ukrainian].12. Brovdii A.M. Osoblyvosti orhanizatsiino-hospodarskykh pravovidnosyn za uchastiu pidpryiemstv lisovoho hospodarstva. Visnyk Natsionalnoho universytetu "Iurydychna akademiia Ukrainy imeni Yaroslava Mudroho". 2012. No. 4 (11). S. 75-85. [in Ukrainian].13. Romaniak M.M. Administratyvnopravovi zasady dozvilnoi diialnosti u sferi zabezpechennia ekolohichnoi bezpeky: avtoref. dys. ... kand. yuryd. nauk: 12.00.07. Irpin, 2010. 18 s. [in Ukrainian].14. Dzhafarova O.V. Dozvilna diialnist u sferi zabezpechennia ekolohichnoi bezpeky: pravovi formy ta yikh vydy. Pravo i bezpeka. 2010. No. 5 (37). S. 66-71. [in Ukrainian].15. Romaniak M.M. Do pytannia pro vyznachennia predmetu dozvilnoi diialnosti v ekolohichnii sferi. Forum prava. 2008. No. 3. S. 433-436. [in Ukrainian].16. Hozjajstvennyj kodeks Ukrainy: Nauchnoprakticheskij kommentarij. Pod obshh. red. A.G. Bobkovoj. Har’kov: Izdatel’ FLP Vapnjarchuk N.N., 2008. 1296 s. [in Russian].17. Shapovalova O.V. Adaptatsiia hospodarskoho zakonodavstva do vymoh YeS shchodo staloho rozvytku. Aktualni problemy prava: teoriia i praktyka: zb. nauk. pr. 2016. No. 32. S. 25-40. [in Ukrainian].18. Shapovalova O.V. Analitychni zasady ekolohizatsii prav subiektiv hospodariuvannia. Aktualni problemy prava: teoriia i praktyka. 2007. No. 10. S. 191-197. [in Ukrainian].19. Vvedenie v ukrainskoe pravo. Pod obshh. red. S.V. Kivalova, Ju.N. Oborotova. 2e izd., pererab. i dop. Odessa: Juridichna literatura, 2009. 768 s.20. Petrov V.V. Jekologicheskoe pravo Rossii: Uchebnik. M.: Bek, 1995. 557 s. [in Russian].21. Jekologicheskoe pravo Ukrainy: ucheb. posob. Pod red. A.P. Get’mana i M.V. Shul’gi. Har’kov: Odissej, 2007. 463 s. [in Russian].22. Shul’ga M.V. Aktual’nye pravovye problemy zemel’nyh otnoshenij v sovremennyh uslovijah. Har’kov: Konsum, 1998 [in Russian].23. Andreitsev V.I. Ekolohichne pravo: Kurs lektsii: navch. posib. Kyiv: Venturi, 1996. 207 s. [in Ukrainian].24. Hetman A.P. Vstup do teorii ekoloho-protsesualnoho prava Ukrainy: navch. posib. Harkiv.: Osnova, 1998. 208 s. [in Ukrainian].25. Hvozdyk P. Mekhanizm uzghodzhennia norm ekolohichnoho zakonodavstva z normamy inshykh haluzei zakonodavstva. Visnyk Kyivskoho natsionalnoho universytetu imeni Tarasa Shevchenka. Yurydychni nauky. 2012. Vyp. 92. S. 13-15. [in Ukrainian].26. Radyk I.L. Pravovi problemy ekolohichnoho litsenzuvannia. Avtoref. dys. ... kand. yuryd. nauk: 12.00.06. Harkiv, 2001. 17 s. [in Ukrainian].27. Apanasenko K.I. Okremi teoretychni pytannia orhanizatsiino-hospodarskykh vidnosyn (na prykladi dozvilnykh vidnosyn u sferi hospodariuvannia). Ekonomika ta pravo. 2016. No. 3. C. 121-133. doi: https://doi.org/10.15407/econlaw.2016.03.121 [in Ukrainian].28. Rozovskij B.G. "Severnyj poljus" jekologicheskogo prava. Visnik Lugans’kogo derzhavnogo universitetu vnutrishnih sprav im. E.O. D³dorenka. 2012. No. 1. S. 188-200 [in Russian].29. Filatova V.K. Pravovi zasady heolohichnoho vyvchennia nadr v Ukraini: monohrafiia. Harkiv: FINN, 2011. 144 s. [in Ukrainian].30. Vikhrov O.P. Hospodarske pravo. Spetsialna chastyna: navch. posibnyk. Kyiv: Slovo, 2004. 344 s. [in Ukrainian].31. Hospodarske pravo: pidruchnyk: u 2 ch. Ch. 2. Za zah. red. V.F. Opryshka ta N.S. Khatniuk. Kyiv: KNEU, 2011. 501 s. [in Ukrainian].32. Bunge N. Policejskoe pravo. Vvedenie v gosudarstvennoe blagoustrojstvo. Tom 1. Kiev: Universitetskaja tipografija, 1873. 355 s. [in Russian].33. Bobkova A.H. Pravove zabezpechennia vykorystannia pryrodnykh resursiv u sferi hospodariuvannia. Pryrodoresursne pravo v systemi prava Ukrainy: istoriia, sohodennia, perspektyvy: zb. materialiv kruhloho stolu, 30—31 zhovtnia 2015 r. Za zah. red. M.V. Shulhy. Harkiv: Oberih, 2015. S. 26-28 [in Ukrainian].34. Romaniak M.M. Pryntsypy dozvilnoi diialnosti u sferi ekolohichnoi bezpeky. Aktualni problemy derzhavnoho upravlinnia: zb. nauk. pr. 2008. No. 2 (34). S. 459-465 [in Ukrainian].35. Kobetska N.R. Kompleksnyi kharakter pravovoho rehuliuvannia vykorystannia pryrodnykh resursiv. Evropský politický a právní diskurz. 2014. Svazek 1. 6. vydání. S. 629-636 [in Ukrainian].36. Khvesyk M.A., Horbach L.M., Kulakovskyi Yu.P. Ekonomikopravove rehuliuvannia pryrodokorystuvannia: Kyiv. Kondor, 2009. 524 s. [in Ukrainian].37. Komarnytskyi V.M., Shevchenko V.I., Yelkin S.V. Ekolohichne pravo: navch. posib. 3-tie vyd. Kyiv: Tsentr navchalnoi literatury, 2006. 224 s. [in Ukrainian].38. Ekolohichne pravo: pidruch. dlia stud. yuryd. spets. vyshch. navch. zakl. Za red. A.P. Hetmana. Harkiv:  Pravo, 2014. 432 s. [in Ukrainian].39. Problemy teorii gosudarstva i prava: uchebnik. Pod red. S.S. Alekseeva. Moskva: Jurid. lit., 1987. 448 s. [in Russian].40. Brovdii A.M. Hospodarsko-pravove zabezpechennia diialnosti derzhavnykh pidpryiemstv lisovoho sektora ekonomiky Ukrainy: avtoref. dys. ... kand. yuryd. nauk: 12.00.04. Harkiv, 2015. 20 s. [in Ukrainian].41. Apanasenko K.I. Pro hospodarsku kompetentsiiu okremykh uchasnykiv dozvilnykh pravovidnosyn u sferi hospodarskoi diialnosti. Rozumovski zustrichi: zb. nauk. pr. Chernihiv: Siverskyi tsentr pisliadyplomnoi osvity, 2016. Vyp. 3. S. 20 [in Ukrainian].42. Vasil’eva M.I. O metodah, sredstvah i sposobah pravovogo regulirovanija jekologicheskih otnoshenij. Jekologicheskoe pravo. 2009. No. 2-3. S. 56-67 [in Russian].